The Relationship Between Sleep Duration and Iron Intake and Hemoglobin Levels in Adolescent Girls - Devieka Rhama Dhanny; Mahfuzhoh Fadillah Heryanda (JURNAL KESMAS DAN GIZI (JKG), 2026)
Background: One of the public health problems that requires greater attention is anemia, especially among adolescent girls, because it has the potential to reduce health status, daily productivity, and disrupt learning concentration. Sleep duration and the adequacy of iron intake are suspected to be factors influencing hemoglobin status. Objective: This study aimed to analyze the relationship between sleep duration and the adequacy of iron intake with hemoglobin levels among adolescent girls. Methodology: This analytic observational study with a cross-sectional design was conducted on 33 female students selected using a total sampling technique. The study was carried out at Sekolah Islam Terpadu Aulia Cendekia during November–December 2025. Sleep duration data were obtained from the Pittsburgh Sleep Quality Index (PSQI) questionnaire, iron intake was collected through the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), and hemoglobin levels were measured using an Hb meter. Data analysis was performed using the Chi-Square test to determine the relationship between variables with SPSS software. Results and Discussion: Most students have abnormal hemoglobin levels (66.7%), insufficient sleep duration (51.5%), and low iron intake (57.6%). The analysis shows a significant relationship between insufficient sleep duration and low hemoglobin levels (p=0.010; OR=9.643), as well as a significant correlation between inadequate iron intake and low hemoglobin levels (p=0.024; OR=7.111). Conclusion: Insufficient sleep duration and low iron intake are significantly associated with hemoglobin levels in adolescent girls; therefore, intervention through nutrition education and improvement of sleep patterns is needed as an effort to prevent anemia.